Ações afirmativas no mercado de trabalho - Oliveira, Renato Neves de (2013)
The Politics of Affirmative Action policies are public and private temporary, intended to mitigate the effects of racial / social that certain groups in society suffer such effects may be due to the discrimination suffered in the past or present. In this sense, the adoption of policies of Affirmative Action has its legal basis in the Brazilian Constitution, as well as in the sphere of International Law of Human Rights, in particular, stand out from the UN Convention on the Elimination of All Forms of Racial Discrimination (1965), the UN Convention on the Elimination of All Forms of Discrimination against Women (1979), the 1966 Covenants: the International Covenant on Civil and Political Rights and the International Covenant on Economic Social and Cultural Rights, and more recently, the Convention that protects people with disabilities, which has constitutional status norm (2007), among other documents. The work presented here addresses the importance of affirmative action policies at the national level, but also in the context of comparative law, in relation to employment in both the public and private spheres, to contribute to a reflection on the importance of social justice in the search for full realization of equal opportunities, so that in fact this condition is met by society. Corroborating this analysis, it is worth noting the chapter on the unanimous decision of ADPF 186, which presents a break with the prevailing standards in society with regard to public policy, embracing a new vision that can be extended to the labor market